Low-cost urban heat environment sensing device with Android platform for digital twin - Yonghun Cho; Sanghyun Kim; Jeongseop Lee; Dongwon Ko; Haesung Lee; Yunju Baek; Myungho Lee (HardwareX)
The proper monitoring of heat and meteorological variables is essential for the well-being of residents of metropolitan areas. It is challenging to configure spatial heat variations in complex urban environments, even though the temporal variation of urban heat flux has been measured at several designated monitoring stations. Neither the budget nor existing techniques for efficient urban heat monitoring are sufficient for a digital twin of the urban heat environment. As a result, we have developed a low-cost monitoring system that can be easily integrated into a portable pedestrian device, kickboard, or electric bike. With this system, citizens can collect information about urban heat, such as air temperature, surface temperature, relative humidity, barometric pressure, light intensity, and micro-geophysical features including topological aspects and mobile information (e.g., three-dimensional accelerations). Citizens can participate in daily scientific activities using these devices, which facilitate data acquisition and information exchange in urban digital twin environments.